Lifetime (Bx) improvement of PV inverter using Si-SiC H-IGBT/Diode: a reliability approach - Ramavath, Muneeshwar; Puvvula Venkata, Rama Krishna (Institute of Advanced Engineering and Science, 2024)
Technological advancements have made it possible to harness the power of renewable energy sources. The efficiency of power electronic devices has increased to almost 98%. In order to reduce the risks of failure and maintain the operation of photovoltaic (PV)-based energy converters, reliable devices are needed. Due to the increasing number of wide-bandgap silicon in electronic converters, the need for more efficient and reliable devices has become more prevalent. However, the cost of these devices is a major issue. Hence, in this work extensive analysis of hybrid silicon (Si)-IGBT and silicon carbide (SiC) antiparallel Diode (H-IGBT/Diode) based PV inverter is proposed to improve the lifetime (Bx). A reliability oriented lifetime assessment is performed on a test case of single stage three kilowatt photovoltaic inverter with 600 V/30 A hybrid switch. Long term mission profile for one year is considered for evaluation at B. V. Raju Institute of Technology (BVRIT), Telangana, India. Finally, B10 lifetime is calculated, comparison analysis is presented between conventional Si-IGBT and proposed Si-SiC H-IGBT/Diode. The results of the study revealed that the H-IGBT exhibited a significant increase in PV inverter reliability.